(untitled) (Revista Brasileira Multidisciplinar, 2022)
Background: Despite the technological advances the zygomatic implants (ZI) and its proven success, this rehabilitation option is sensitive, not a routine in dental practice, requiring technical mastery, surgical experience, and in-depth anatomical knowledge, which makes it quite susceptible to complications. In addition, little is discussed about these disorders, whether immediate or late, although they are essential knowledge for the surgeons who perform this procedure. Aim: The objective of the study was to answer the question through literature review: "Are there surgical complications in zygomatic implants?" As well as to argue the main intercurrences found. Material and Methods: The review of the literature was conducted on PubMed/Medline, Cochrane and SciELO using the descriptors: “Complications” or “Failure” and “Zygomatic Implants”. The included articles were observational studies that related ZI and complications. The initial research identified 448 articles, but 42 of them that mentioned complications associated with ZI were considered in this study. Results: The most common complication is sinusitis followed by peri-implantitis, problems with the prosthetic connection, fistula towards the implant, paresthesia, hematoma, lip laceration, ecchymosis, penetration of the orbital cavity, aspergillosis, intracranial penetration, and intraorbital hemorrhage. 44 out of 2835 ZIs placed in immediate or late loading were lost (1.5%). There were 223 minor or major complications in the 2827 implants (7.86%). Conclusions: The low morbidity of this treatment for maxillary atrophy, there are some immediate and late complications to be considered in the choice of rehabilitation treatment and that these should be reported preoperatively to the patients.